2022
DOI: 10.1063/5.0077448
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of nature of excitons in PPDT2FBT and effect of optical interference

Abstract: Electroabsorption (EA) measurements can be used to identify the type of excitons contributing to the absorption spectra of semiconductors. However, the shape of the EA spectrum may vary depending on the mode of measurement due to the optical interference effects. Analysis without considering these effects may lead to erroneous conclusions. In this work, we present EA measurements and analysis for reflection mode measurements considering optical interference effects. We compared the inferences with transmission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Therefore, the presence of acceptor in the blend helps in formation of interfacial charge transfer excitons [3]. In our earlier studies [14], we showed that, for pristine PPDT2FBT, the generated excitons had mixed nature i.e. both Frenkel and charge transfer (CT) characteristics.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Therefore, the presence of acceptor in the blend helps in formation of interfacial charge transfer excitons [3]. In our earlier studies [14], we showed that, for pristine PPDT2FBT, the generated excitons had mixed nature i.e. both Frenkel and charge transfer (CT) characteristics.…”
Section: Resultsmentioning
confidence: 92%
“…In the case of Frenkel excitons, the change in polarizability (∆P ) between the ground state and excited state energy level is significant. Whereas the change in the dipole moment (∆µ) indicates the formation of CT excitons in a transition [8,14]. Both these contributions have distinct lineshape, revealing the nature of the exciton related to any particular transition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation